Analysis of Islamic Banking Supervision in Indonesia (A Study of the Economic Thoughts of Muhammad Syafi’i Antonio) - Fahrurrozi (Universitas Muhammadiyah Palu, 2025)
The development of Islamic banking in Indonesia cannot be separated from the global progress of Islamic banking. The idea of establishing an Islamic bank emerged alongside the growth of Islamic banking on the international stage, which began in the 1970s, as previously mentioned. The emergence of Islamic banks globally influenced financial institutions in Indonesia. However, Syafi’i Antonio explains that the specific initiative to establish an Islamic bank in Indonesia only began in 1990. On August 18-20, 1990, the Indonesian Ulema Council (MUI) held a workshop on Bank Interest and Banking in Cisarua, Bogor, West Java. The outcomes of this workshop were further discussed during the Fourth National Conference of the MUI held at Sahid Hotel, Jakarta, on August 22-25, 1990. Based on the mandate of the Fourth National Conference of the MUI, a working group was formed to establish an Islamic bank in Indonesia. Oversight of banking operations became a significant topic in the development of Islamic banking in Indonesia. This is primarily due to the unique oversight method implemented by the National Sharia Council (DSN) under the supervision of Bank Indonesia (BI). Muhammad Syafi’i Antonio (MSA), a Muslim intellectual specializing in Islamic economics, particularly Islamic banking, conducted an in-depth study on all aspects of Islamic banks, including the supervision of banking management. What makes this topic compelling is MSA’s proposal of various alternatives for Islamic banks, focusing particularly on the aspect of supervision. Through a sharia-based approach authorized by the country's constitution, MSA compares personal compliance of banking practitioners with institutional professionalism. This method proves to be highly effective in implementing layered oversight for Islamic banks. Therefore, the author finds it intriguing to bring MSA’s thoughts into a thesis titled An Analysis of Islamic Banking Supervision in Indonesia (A Study of Muhammad Syafi’i Antonio’s Islamic Economic Thought). This research specifically aims to uncover MSA’s remarkable thoughts, as someone who has both theoretical and practical expertise in Islamic banking and its supervisory mechanisms, while also serving as a strategic step to understand the regulations established by Islamic law (sharia) and statutory laws regarding supervisory patterns for Islamic banking practitioners.